PENGARUH ACADEMIC RESILIENCE DAN PSYCHOLOGICAL SAFETY TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI KELAS XI SMA NEGERI 1 RAJAGALUH - Ridha Fauziyah, Leila; Roro Suci Nurdianti, Raden; Fitriana Afriza, Edi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the fact that some students who had not yet achieved mastery in summative assessment in economic subjects. This condition may be attributed to students lack of resilience in dealing with academic pressures, as well as a learning environment that does not adequately support them psichologically to participate actively during the learning process. Therefore, these two factors are considered important insupporting students learning achievement. Based on this background, the study aimed to determine the effect of academic resilience and psychological safety on the learning archievement of grade XI students studying economics subjects. This research employed a quantitative method with a survey approarch. The population consisted of 427 XI grade students. The research sample consisted of 247 students selected using purposive sampling technique. Data were collected through questionnaires. The collected data were analyzed using multiple linear regression. Pior to hypothesis testing, the data were subjected to prerequisite test. Hypothesis testing was conducted through partial and simultaneous tests. The result of the study indicate that academic resilience and psychological safety had a significant effect on students learning achievement, both partially dan simultaneously. These findings suggest that the higher the levels of academic resilience and psychological safety possessed by students, the higher their learning achievement will be.